2011
DOI: 10.3892/mmr.2011.533
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-mediated apoptosis via activation of the mitochondrial-dependent pathway in MG-63 osteosarcoma cells

Abstract: Abstract. Quercetin (a natural polyphenolic compound) is a polyphenolic flavonoid compound found in a variety of plants. It has been demonstrated to exert cytostatic activity against a variety of human cancer cell lines, including the human osteosarcoma cell line, MG-63. However, its effects on osteosarcoma cell apoptosis are still undefined. The present study was undertaken to examine the effect of quercetin on cell viability, apoptosis and mitochondrial membrane potential, and to determine the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The proapoptotic activity of quercetin against cancer cells has been well documented, e.g., in leukemia (HL-60) [35], osteosarcoma (MG-63) [36], colon (LoVo) [37], breast (MCF-7, U937) [3739], brain (MOGGCCM, T98G) [40–42], and lung (NCI-H209) [43] cell lines. Since quercetin has been examined in a variety of cancer cells, it is important to understand the effect of the flavonoid also on normal, non-malignant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proapoptotic activity of quercetin against cancer cells has been well documented, e.g., in leukemia (HL-60) [35], osteosarcoma (MG-63) [36], colon (LoVo) [37], breast (MCF-7, U937) [3739], brain (MOGGCCM, T98G) [40–42], and lung (NCI-H209) [43] cell lines. Since quercetin has been examined in a variety of cancer cells, it is important to understand the effect of the flavonoid also on normal, non-malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have proposed the mechanisms involved in the proapoptotic properties of this flavonoid consisting in activation of kinases, downregulation of survival pathways, mitochondrial potential perturbation, release of cytochrome c , and, in consequence, activation of caspase-3 and caspase-9 [18, 22, 35, 36, 38]. Experiments have shown that micromolar concentrations of quercetin in the range of 29–150 μmol/l can induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the overall biological impact of quercetin remains controversial, mostly due to the limited information about its bioavailability, endogenous dynamics, and relative contribution of different types of conjugates. Some studies have showed that quercetin can mediate cancer cell apoptosis [22,25]. Furthermore, these investigations have indicated that quercetin can selectively induce apoptosis of cancer cells and not normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, in ovarian cancer cells, low concentrations of quercetin attenuate the therapeutic effects of cisplatin by reduced production of intracellular reactive oxygen species ( Li et al, 2014 ). Studies also showed that quercetin suppresses osteosarcoma cell proliferation ( Liang et al, 2011 ; Suh et al, 2010 ). However, a few researches on the effects of combined quercetin and chemotherapy on osteosarcoma, especially on their regulatory mechanism were conducted.…”
Section: Introductionmentioning
confidence: 99%